1988
DOI: 10.1111/j.1471-6712.1988.tb00026.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Episiotomy and Spontaneous Tears of Perineum during Childbirth

Abstract: While episiotomy is a common operation during delivery little is known of its benefits compared with spontaneous tears. This study was designed to evaluate and compare episiotomies and spontaneous tears. The sample comprised 205 primiparas, 157 with episiotomies and 48 with spontaneous tears. Women with episiotomies expressed more discomfort, perineal complications were more pronounced and prolonged, and fewer were able to participate in the post-partum exercises. Furthermore, delayed healing was recorded for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
1
2

Year Published

1991
1991
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 15 publications
4
10
1
2
Order By: Relevance
“…However, comparison of the antepartum and postpartum muscle function scores suggested that the degree to which women regained perineal muscle function after birth was positively related to perineal trauma at delivery: those with the least perineal trauma (the intact and cesarean groups) had the greatest positive change in scores. The finding that the group of women who received an episiotomy was the only group to exhibit a net loss of perineal muscle function after delivery is consistent with that of Rockner et al 19 and adds further support to the contention that routine episiotomy or episiotomy to prevent a laceration may actually contribute to a decline in function.…”
Section: Discussionsupporting
confidence: 84%
“…However, comparison of the antepartum and postpartum muscle function scores suggested that the degree to which women regained perineal muscle function after birth was positively related to perineal trauma at delivery: those with the least perineal trauma (the intact and cesarean groups) had the greatest positive change in scores. The finding that the group of women who received an episiotomy was the only group to exhibit a net loss of perineal muscle function after delivery is consistent with that of Rockner et al 19 and adds further support to the contention that routine episiotomy or episiotomy to prevent a laceration may actually contribute to a decline in function.…”
Section: Discussionsupporting
confidence: 84%
“…During this time, the number of partial or total ruptures of the anal sphincter fell from 1.6 to 1.1 %, but this reduction is not significant (p > 0.05). These results are in accordance with those of Rockner et al [8,9], A decrease in the episiotomy frequency does not seem to be disadvantageous for the mother since the frequency of sphincter ruptures is unaltered. The patient comfort increases and the perineal healing progresses better if an episiotomy is avoided.…”
Section: Discussionsupporting
confidence: 82%
“…Although it is said to be difficult to clearly attribute rates of infection to episiotomy (Thacker and Banta, 1983). The infection rate obtained in this study is lower than that obtained by Larsson et al (1991), with infection rate at 10% and Rockner et al (1988), with 22% infection rate. They had microscopy, culture and sensitivity studies done on the swabs taken from the infected sites and appropriat e antibiotic regimen was administered based on the sensitivity results.…”
Section: Discussioncontrasting
confidence: 80%